Desempenho de concretos com elevados níveis de substituição do cimento Portland por fíler calcário em relação à corrosão desencadeada por cloretos - Cândido, Taíssa Guedes (2023)
There is growing concern about the CO2 emissions produced by Portland cement production. As a result, various strategies have been developed to mitigate the negative effects. One of the most widely adopted approaches is to replace clinker with mineral additions. However, it is important that low-cement concretes also exhibit satisfactory durability, especially when it comes to chloride-induced corrosion. Despite efforts to partially replace Portland cement with inert materials, there is still no consensus on the effectiveness of such measures. This study aimed to evaluate the corrosion induced by chlorides in low-binder concrete, using limestone filler as an addition and partial substitute for Portland cement. Three different concrete formulations were tested, each with different levels of Portland cement content: 350 kg/m³ (referred to as C350), 250 kg/m³ (C250), and 150 kg/m³ (C150). These levels represent reductions of approximately 29% and 57%, respectively. The C250 displayed superior overall performance in terms of mechanical strength, water absorption, and ultrasonic pulse speed. While C150 exhibited a lower compressive strength compared to the other formulations, it still surpassed the minimum recommended value for concrete structures outlined by NBR 6118 (ABNT, 2023). Overall, the reference concrete demonstrated better resistance to chlorides due to its superior binding capability. This implies that chemical factors, such as the availability of aluminates and hydroxides, played a decisive role in the chloride diffusion coefficient. Under controlled laboratory conditions that did not involve exposure to wetting and drying cycles (such as tidal splashes or rain), the steel incorporated in C250 exhibited corrosion rates similar to those of the reference concrete. This study concludes that using concrete with reduced Portland cement content may be feasible, but its durability properties must be carefully evaluated.